ANALISIS KEBUTUHAN SISWA SEBAGAI ACUAN MENGEMBANGKAN BUKU PENGAYAAN FISIKA BERKONTEKS KEARIFAN LOKAL PERAHU TRADISIONAL - Dani, Rahma; Jufrida, Jufrida; Wijaya, Nabilla Eka (EduFisika: Jurnal Pendidikan Fisika, 2022)
This examine pursuits to research students' wishes for coaching substances used in the physics learning system. This studies is an exploratory descriptive studies with 30 students majoring in science majoring in 11th grade SMA. The studies records became obtained from observation and filling out a wishes questionnaire. observation consequences show that physics learning contains extra texts and physics formulation, but due to the restricted mastering time in each assembly, it's far hard for teachers to provide an explanation for examples of physics concepts determined in normal lifestyles to students. The consequences of the questionnaire analysis display that scholars want teaching substances in the form of enrichment books as a aid within the studying process and can be used independently or with teacher assistants at school.